Radiofrequency ablation for treatment of refractory gastric antral vascular ectasia (with video) - Jana, Tanima; Thosani, Nirav; Fallon, Michael B.; Dupont, Andrew W.; Ertan, Atilla (Endoscopy International Open, 2015)
Background and study aims: Gastric antral vascular ectasia (GAVE) is a known cause of gastrointestinal bleeding and chronic iron deficiency anemia. Endoscopic therapy with argon plasma coagulation (APC) is widely used for treatment of GAVE, but most patients continue to require repeated blood transfusions and multiple endoscopic procedures (refractory GAVE). We describe our initial experience regarding safety and efficacy of radiofrequency ablation (RFA) therapy in treating patients with refractory GAVE. Patients and methods: We prospectively enrolled seven patients with refractory GAVE who had multiple prior treatments with APC. These patients were treated with RFA (HALO90 ULTRA Ablation Catheter System; Covidien, GI Solutions, Sunnyvale, CA) at Ertan Digestive Disease Center at our tertiary University Hospital. Results: Seven patients underwent a total of 12 RFA procedures for treatment of refractory GAVE. The median number of RFA procedures was 2 (Range, 1 – 3). Average pre- and post-procedural hemoglobin were 9.3 g/dL and 10.16 g/dL, respectively. Five of seven patients (71 %) were transfusion-free after the RFA treatments while two patients continued to require blood transfusions. There were no complications in this series. Conclusion: RFA can be an effective alternative to APC for treatment of GAVE refractory to previous endoscopic therapy. Additional studies are needed to identify which subset of patients will benefit the most with RFA treatment.